2003
DOI: 10.1128/jvi.77.20.11060-11071.2003
|View full text |Cite
|
Sign up to set email alerts
|

Junonia coenia Densovirus-Based Vectors for Stable Transgene Expression in Sf9 Cells: Influence of the Densovirus Sequences on Genomic Integration

Abstract: The invertebrate parvovirus

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 37 publications
6
49
0
Order By: Relevance
“…Currently, the only known animal DNA virus to exhibit site-directed integration is adenoassociated virus (AAV), where nonhomologous recombination into different locations of the AAVS1 domain in human chromosome 19 involves interactions between virus-encoded proteins, palindrome-forming terminal inverted repeats in the viral genome, and host cell machinery (9,18,19,24,44). The integration of another group of parvoviruses (densoviruses) that infect insects may also involve unknown host cell factors interacting with viral sequences (8).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the only known animal DNA virus to exhibit site-directed integration is adenoassociated virus (AAV), where nonhomologous recombination into different locations of the AAVS1 domain in human chromosome 19 involves interactions between virus-encoded proteins, palindrome-forming terminal inverted repeats in the viral genome, and host cell machinery (9,18,19,24,44). The integration of another group of parvoviruses (densoviruses) that infect insects may also involve unknown host cell factors interacting with viral sequences (8).…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the polypeptide obtained by Hayakawa et al [14] from the expression of the N-terminal 1,000 nucleotides of BmDNV-2 VD1-ORF1 indicated that the polypeptide's C-terminus is the basic region with an isoelectric point of around 8. 16. We speculated that this basic region had a similar function as histone in eukaryotic chromosomal organization and therefore was the viral nucleoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the observation that several structural proteins translate from one ORF is very common in parvoviruses. For instance, VPs of densonucleosis viruses of Galleria mellonella , Junonia coenia and Mythimna loreyi are all translated from one ORF by a leaky scanning mechanism [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…We also describe a new vector for use in transient transfection of cell lines of Spodoptera and related species. This vector is a pBAC3.6e vector derivative (Frengen et al, 1999) carrying a GFP marker under the control of an insect promoter, the densoviral P9 promoter (Bossin et al, 2003), which is functional in numerous Lepidoptera including B. mori. Since it is a BAC vector, it can accommodate large genomic inserts.…”
Section: Introductionmentioning
confidence: 99%